The haunting of Sunshine girl. Book one - McKenzie, Paige; Sheinmel, Alyssa B.; Hagen, Nick (McKenzie, Paige. Haunting of Sunshine girl, 2015)
Shortly after her sixteenth birthday, Sunshine Griffith and her mother Kat move from sunny Austin, Texas, to the rain-drenched town of Ridgemont, Washington. Though Sunshine is adopted, she and her mother have always been close, sharing a special bond filled with laughter and inside jokes. But from the moment they arrive, Sunshine feels her world darken with an eeriness she cannot place. And even if Kat doesn't recognize it, Sunshine knows that something about their new house is just ... creepy.